The effect of stocking density and crude protein level on performance, carcass characteristics, nitrogen use, and ammonia emissions of the Indonesian native chickens - Hantoro, F. R. P.; Sunarti, D.; Yudiarti, T.; Sumarsih, S.; Sinurat, A. (Diponegoro University, 2024)
This was study aimed to investigate the impact of stocking density and crude protein level on the performance, carcass characteristics, nitrogen (N) use, and ammonia emissions of Sentul Selected (Sensi)-1 Agrinak chickens. A total of 504 chickens were used in the 70-day analysis using a random ized block design with factorial pattern of 3 × 3 which was arranged in nine treatments and four repli cates. The administered treatment covered two factors, including stocking density (A) and crude pro tein level (B). The treatments were administered when chickens reached 5 weeks of age. The results showed that different stocking density significantly influenced (p<0.05) the average weekly feed con sumption per chicken at 6, 7, 8, and 9 weeks, but not at 5, 6, and 10 weeks. However, varying crude protein levels showed no significant effect on carcass weight, giblet weight, and total edible parts. There was also no significant interaction observed between stocking density and crude protein level in relation to carcass weight and edible parts. Furthermore, no significant differences were found in giblet and carcass weights between the two groups (p>0.05). The results showed that feeding Sensi-1 Agrinak chickens with a lower crude protein level of up to 14% did not compromise their performance, meat quality, protein digestibility, or ammonia emissions, but affected carcass characteristics.